Cnages in activity limitations and predictors of functional outcome of patients with spinal cord injury following in patient rehabilitation - C. Joseph; G. Mji; S. Statham; N. Mlenzana; C. de Wet; A. Rhoda (AOSIS, 2013)
The purpose of this study was to investigate the changes in the activity limitations of patients following in-patient rehabilitation and the factors influencing functional ability as measured by the Spinal Cord independence measure III (SCIM III). A longitudinal study design was utilised to study the change in functional abilities of patients with spinal cord injury between admission and discharge. A convenient sampling strategy was employed, in which every consecutive patient admitted to the rehabilitation centre within a three-month period was eligible for the study. Demographic-, medical, and process of rehabilitation data were collected and collated from the patients' medical records using a data gathering sheet that was validated and tested for reliability. functional abilities were measured by the SCIM III. Seventy-six patients met the inclusion criteria, consisting of 58 paraplegics and 18 tetraplegics. The mean age of this cohort was 34.14 years. A significant difference (p<0.001) in functional ability was detected for the total sample, with only 12.5% of patients independent in walking ability and 28.12% in stair management. four (4) factors were found to be predictors of functional outcomes on bivariate analysis, but when considered together in a multiple regression model, only functional status on admission remained correlated to functional outcomes. Conclusion and implication for practice: Significant improvement in functional abilities of persons with spinal cord injury following in-patient rehabilitation was observed. however, mobility and stair-management limitations were the most prevalent at discharge. lastly, a lower functional status should be better targeted to optimise functional ability in the future. future research should be directed towards illuminating whether personal factors or rehabilitation inefficiencies are responsible for the limitations observed at discharge.